2021
DOI: 10.1039/d0cs01339k
|View full text |Cite
|
Sign up to set email alerts
|

Beyond hydrogen bonding: recent trends of outer sphere interactions in transition metal catalysis

Abstract: The implementation of interactions beyond hydrogen bonding in the 2nd coordination sphere of transition metal catalysts is rare. However, it has already shown great promise in last 5 years, providing new tools to control the activity and selectivity as here reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 177 publications
0
36
0
Order By: Relevance
“…Significant advances have been made in creating these artificial enzymes, as summarized [211][212][213][214][215][216][217][218][219][220][221] in several excellent reviews. It turns out that second-sphere coordination has been exploited widely as an emerging strategy for designing artificial enzymes by encapsulating catalysts inside molecular containers, leading to high efficiencies and excellent regio-and stereoselectivities being achieved at the catalytic centers.…”
Section: Catalysismentioning
confidence: 99%
“…Significant advances have been made in creating these artificial enzymes, as summarized [211][212][213][214][215][216][217][218][219][220][221] in several excellent reviews. It turns out that second-sphere coordination has been exploited widely as an emerging strategy for designing artificial enzymes by encapsulating catalysts inside molecular containers, leading to high efficiencies and excellent regio-and stereoselectivities being achieved at the catalytic centers.…”
Section: Catalysismentioning
confidence: 99%
“…On the other hand, less-conventional non-covalent interactions have also been exploited for substratepreorganization catalysis such as halogen bonding, pi interactions, amongst others. [47] An appealing type of non-covalent interaction is the kinetically-labile coordination between a metalloporphyrin and a polarcoordinating molecule (Figure 2, top). [48] In this type of interaction, the metal (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As transition metal complexes make up the vast majority of such catalysts, classical means for their modification through ligand design, the choice of and number of metal centres, and external influences such as light or electric current have received the majority of this research attention [1–6] . However, studies into ligand designs have also shown that metal‐based reactivity can be influenced by ligand‐based bond‐breaking and bond‐forming, secondary coordination sphere interactions, and ligand‐based redox reactions [7–10] . These are classed as cooperative modes of action.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 , 3 , 4 , 5 , 6 ] However, studies into ligand designs have also shown that metal‐based reactivity can be influenced by ligand‐based bond‐breaking and bond‐forming, secondary coordination sphere interactions, and ligand‐based redox reactions. [ 7 , 8 , 9 , 10 ] These are classed as cooperative modes of action. An emerging alternative to these more established classes of non‐innocent ligands is the installation of a single‐site ambiphilic centre that provides reactivity that is complementary to that of the transition metal.…”
Section: Introductionmentioning
confidence: 99%